2018
DOI: 10.1039/c8tc00157j
|View full text |Cite
|
Sign up to set email alerts
|

A compliant, self-adhesive and self-healing wearable hydrogel as epidermal strain sensor

Abstract: A compliant, self-adhesive and self-healing epidermal strain sensor that shows excellent sensing performance at ultra-low and high strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 42 publications
0
151
1
Order By: Relevance
“…More importantly, DA provides a new perspective for the development of wearable strain sensors with excellent self‐adhesive properties. For instance, Liu et al reported a hydrogel‐based self‐adhesive and self‐healing epidermal strain sensor by adding Polydopamine (PDA) to PVA; the developed sensor can detect minute epidermal deformations (0.1% strain) and large body movements (10–75% strain) such as throat vibration and finger bending. In addition, it can be used in the field of low‐intensity strain sensing.…”
mentioning
confidence: 99%
“…More importantly, DA provides a new perspective for the development of wearable strain sensors with excellent self‐adhesive properties. For instance, Liu et al reported a hydrogel‐based self‐adhesive and self‐healing epidermal strain sensor by adding Polydopamine (PDA) to PVA; the developed sensor can detect minute epidermal deformations (0.1% strain) and large body movements (10–75% strain) such as throat vibration and finger bending. In addition, it can be used in the field of low‐intensity strain sensing.…”
mentioning
confidence: 99%
“…Highly stretchable resistive type strain sensors have been developed using mechanisms such as crack propagation in thin films or the disconnection/tunnelling effect between conductive fillers [362,363]. Materials such as liquid metals [59,60,[370][371][372], metal nanowires/nanostructures [315,[373][374][375], carbon black [100,101], CNT [90,[377][378][379][380][381], graphene [94,[382][383][384], ionic liquids [385][386][387][388] and hydrogels [116,329,[389][390][391] have been used to fabricate resistive strain sensors.…”
Section: Resistive Strain Sensorsmentioning
confidence: 99%
“…Hydrogel strain sensors made of ionic conductors gained a huge interest in the recent past due to their excellent transparency, biocompatibility and self healing properties [116,329,[389][390][391]. A self healing hydrogel-based strain sensor able to withstand strains up to 1000% with a gauge factor of 1.51 is displayed in Figure 8a [116].…”
Section: Resistive Strain Sensorsmentioning
confidence: 99%
“…Thus, a moderate network density induced by the copolymerization of allyl cellulose and acrylic acid contributed to the acquisition of remarkable mechanical performance by the CHs. In addition, low-modulus sensors would more easily detect micro strains of the skin, and the combination of high stretchability and low modulus would make hydrogels well adaptable to the epidermis [23]. Obviously, CH3 had a low tensile modulus (35 KPa) compared to human skin (2-80 KPa of modulus for the dermis, 140-600 KPa of modulus for the epidermis).…”
Section: Mechanical Performancementioning
confidence: 99%
“…In our previous study, ultra-stretchable cellulose ionic hydrogels were prepared by using (NH 4 ) 2 S 2 O 8 to initiate free radical polymerization, then using NaCl to induce physical cross-linking [22]. However, although high mechanical performance was obtained, there remains the challenge of combining the properties of transparency, high sensitivity, and high mechanical performance to construct wearable sensors that imitate the human skin (with 2-80 KPa of modulus for the dermis and 140-600 KPa of modulus for the epidermis) [23][24][25]. Cellulose-based hydrogels in which cellulose is the main scaffold and a synthetic polymer is blended in the system have become a notably attractive option in recent years, because they have many advantages, such as adjustable mechanical properties [19,26,27].…”
Section: Introductionmentioning
confidence: 99%